2020
DOI: 10.3389/fpsyt.2019.00972
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and the Psychological Recovery Process Among Informal Caregivers of Inpatients Suffering From Depressive Disorder: A Descriptive Exploratory Study

Abstract: Background: Informal caregivers of people suffering from depressive disorders go through a psychological recovery process. This process is dynamic, deep, catalyzed by hope and optimism and characterized by stages from which specific needs ensue. This study aimed to describe the stages of the psychological recovery process and the level of optimism among informal caregivers of psychiatric inpatients suffering from depressive disorders in order to provide adapted nursing support and psychoeducation and facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…11 These have highlighted various lived experiences, each of which offer difference experiences dependent on the disease state of individuals. Whilst these are recurrent themes such as constant burden, 8,10 knowledge 9,11 and role reversal, 11 there are also differences related to reward, worth and pleasure which have been associated with caregiving for people with terminal illness, 12,13 but also fear and concern regarding harm, associated with caregiving for people with cognitive impairment. 14,15 Various sociological models have been developed to explain caregiver-care recipient dyads.…”
Section: Introductionmentioning
confidence: 99%
“…11 These have highlighted various lived experiences, each of which offer difference experiences dependent on the disease state of individuals. Whilst these are recurrent themes such as constant burden, 8,10 knowledge 9,11 and role reversal, 11 there are also differences related to reward, worth and pleasure which have been associated with caregiving for people with terminal illness, 12,13 but also fear and concern regarding harm, associated with caregiving for people with cognitive impairment. 14,15 Various sociological models have been developed to explain caregiver-care recipient dyads.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the channels used to share the survey (e.g., online social networks) specifically targeted informal caregivers in contact with informal caregivers’ associations or with health professionals. Study participants were better educated than is usually reported ( 51 ), suggesting that some groups were missed, possibly due to digital poverty or lack of health literacy skills. Moreover, the time spent providing care or support to the care recipient and the frequency of contact between the informal caregiver and the care recipient were not used as eligibility criteria because the pandemic context may have affected them drastically.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, caregivers were not selected based on a specific illness or medical condition of the care-recipients. Previous evidence has frequently focused on examining informal caregiver outcomes for caregivers with specific diseases [8,11,19]. Accordingly, this analysis provides new insights to the wider community.…”
Section: Discussionmentioning
confidence: 99%
“…Given these contextual factors, this is a valuable model when investigating the caregiving dyad. However, there remains limited evidence how these change over time [19,20].…”
Section: Introductionmentioning
confidence: 99%